Effect of Bimaxillary Rotational Setback Surgery on Upper Airway Structure in Skeletal Class III Deformities. Issue 2 (February 2015) - Hsieh, Yuh-Jia; Chen, Yi-Chieh; Chen, Yin-An; Liao, Yu-Fang; Chen, Yu-Ray
<x xml:space="preserve">Abstract</x> Background: Upper airway narrowing has been a concern of mandibular setback. The aims of this study were (1) to evaluate the effect of bimaxillary rotational setback surgery on upper airway structure in patients with skeletal class III deformities, and (2) to compare the preoperative and postoperative upper airways of class III patients with age- and sex-matched class I control subjects. Methods: The upper airways of 36 adults who consecutively underwent bimaxillary rotational setback surgery for skeletal class III deformities were assessed by means of cone-beam computed tomography before and at least 6 months after surgery. Results were compared with those of age- and sex-matched control subjects with skeletal class I structure. Results: Before surgery, the class III patients had significantly larger velopharyngeal, oropharyngeal, and hypopharyngeal volumes than did the control subjects (all p < 0.01). The velopharyngeal, oropharyngeal, and hypopharynx volumes decreased significantly after surgery (all p < 0.01). The postoperative airways of class III patients were similar with regard to velopharyngeal, oropharyngeal, and hypopharyngeal volume (all p > 0.01) compared to control subjects. The postoperative velopharyngeal and oropharyngeal airway volumes were associated with the baseline airway volume (p < 0.001) and horizontal movement of the soft palate (p < 0.01). Conclusion: These results suggest that upper airway volume is decreased after bimaxillary rotational setback surgery for skeletal class III deformities, but is not smaller than in normal controls, and the postoperative upper airway volume is related to airway volume at baseline and changes in the surrounding structures. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.